2020
DOI: 10.3390/proteomes8030016
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Identification of the Rhodnius prolixus Midgut Proteome Unravels a Sophisticated Hematophagic Machinery

Abstract: Chagas disease is one of the most common parasitic infections in Latin America, which is transmitted by hematophagous triatomine bugs, of which Rhodnius prolixus is the vector prototype for the study of this disease. The protozoan parasite Trypanosoma cruzi, the etiologic agent of this disease, is transmitted by the vector to humans through the bite wound or mucosa. The passage of the parasite through the digestive tract of its vector constitutes a key step in its developmental cycle. Herewith, by a using high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(78 citation statements)
references
References 56 publications
4
70
0
Order By: Relevance
“…In the context of the search for proteins possibly implicated in the triatomine immune system, we also detected three annexins (described initially in R. prolixus) in our proteome samples. After comparing these three annexins with sequences from Ribeiro et al (2014), Vieira et al (2015) and Ouali et al (2020) through Basic Local Alignment Search Tool (BLAST) analyses, we noted that these authors already found them confirming previous inferences from the complete genome sequence. Annexins are a family of proteins that are associated with many biological events, including calcium-binding, interaction with membranes, intracellular vesicle trafficking, arachidonic acid release, leukocyte migration, and that also affects several mediators involved in the inflammatory response including cyclo-oxygenase-2 (Cox-2) and inducible nitric oxide synthase (Minghetti et al, 1999;Ferlazzo et al, 2003;Rescher and Gerke, 2004;Gavins and Hickey, 2012).…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…In the context of the search for proteins possibly implicated in the triatomine immune system, we also detected three annexins (described initially in R. prolixus) in our proteome samples. After comparing these three annexins with sequences from Ribeiro et al (2014), Vieira et al (2015) and Ouali et al (2020) through Basic Local Alignment Search Tool (BLAST) analyses, we noted that these authors already found them confirming previous inferences from the complete genome sequence. Annexins are a family of proteins that are associated with many biological events, including calcium-binding, interaction with membranes, intracellular vesicle trafficking, arachidonic acid release, leukocyte migration, and that also affects several mediators involved in the inflammatory response including cyclo-oxygenase-2 (Cox-2) and inducible nitric oxide synthase (Minghetti et al, 1999;Ferlazzo et al, 2003;Rescher and Gerke, 2004;Gavins and Hickey, 2012).…”
Section: Introductionsupporting
confidence: 67%
“…To integrate the proteome of this study to previous knowledge, we gathered the sequences from our proteome samples with the datasets of R. prolixus from Ribeiro et al (2014), Vieira et al (2015) retrieved from the Bioinformatics Resource for Invertebrate Vectors of Human Pathogens (VectorBase, 4 ), and Ouali et al (2020) from ProteomeXchange Consortium. We retrieved the equivalent of UniprotKB accession considering an identity region (BLASTp) of 70% of the query sequence with a similarity ≥ 80% in the case of sequences from Ribeiro et al (2014) and Vieira et al (2015).…”
Section: Data Analysesmentioning
confidence: 99%
See 3 more Smart Citations